New Opportunities: Second Harmonic Generation of Boron‐Doped Graphene Quantum Dots for Stem Cells Imaging and Ultraprecise Tracking in Wound Healing. (19th July 2019) - Qi, Xiaoyang; Liu, Hanping; Guo, Wenjing; Lin, Wei; Lin, Baoping; Jin, Ying; Deng, Xiaoyuan
Abstract: Second harmonic generation (SHG) has recently emerged, having the advantages of no bleaching, no blinking, and no signal saturation, as well as a high signal to‐noise ratio compared to fluorescence. Existing SHG probes are based on heavy metal or organic dye molecules, which have the shortcomings of toxicity, a large size, or photoinstability. To address the urgent need for long‐term tracking and imaging in organisms, boron‐doped graphene quantum dots (B‐GQDs), a highly biocompatible graphene based with a strong and photostable SHG signal is first synthesized and is further applied for stem cell imaging and tracking in wounds. The results demonstrate the possibility of stem cell internalization of B‐GQDs as a SHG probe and show no hindering of the stem cell's central physiological activities such as differentiation. Most importantly, B‐GQDs are successfully tracked in skin tissue in vivo after the labeled mouse mesenchymal stem cells being implanted over 35 days. This work will inspire the development of doped graphene quantum dot materials and promote the broad use of B‐GQDs in future molecular imaging, drug delivery, and stem cell therapy. Abstract : Boron‐doped graphene quantum dots (B‐GQDs) with a strong second harmonic generation (SHG) signal are first synthesized. Mouse mesenchymal stem cells with internalized B‐GQDs are seeded on an acellular dermal matrix, which are subsequently transplanted to the mouse skin wound site. The B‐GQDs with SHG are applied for stem cell imaging and tracking in wound healing in vivo.